The M-domain Controls the Hsp104 Protein-remodeling Activity in an Hsp70/Hsp40-dependent Manner - Sielaff, Bernhard (2010)
Yeast Hsp104 is a ring-forming, ATP-dependent protein disaggregase that, together with the cognate Hsp70 chaperone system, has the remarkable ability to rescue stress damaged proteins from a previously aggregated state. Both up-stream and down-stream functions for the Hsp70 system have been reported, but it remains unclear how Hsp70/Hsp40 is coupled to the Hsp104 protein remodeling activity. Hsp104 is a multi-domain protein that possesses an N-terminal domain, an M-domain, and two tandem AAA+ domains. The M-domain forms an 85-Å long coiled-coil and is a hallmark of the Hsp104 chaperone family. While the 3D structure of Hsp104 has been determined, the function of the M-domain is unclear. Here, we demonstrate that the M-domain is essential for protein disaggregation but dispensable for the Hsp104 ATPase and substrate translocating activities. Remarkably, replacing the Hsp104 M-domain against that of bacterial ClpB, and vice versa, switches the species-specificity so that our chimeras now cooperate with the non-cognate Hsp70/DnaK chaperone system. Our results demonstrate that the M-domain controls the Hsp104 protein remodeling activities in an Hsp70/Hsp40-dependent manner, which is required to unleash the Hsp104 protein disaggregating activity.